Better Together: An Examination of Collaborative Publishing between Librarians and STEM and Health Sciences Faculty. - Molly Higgins; Jennifer A. DeVito; Sally Stieglitz; Robert Tolliver; Clara Y. Tran (Issues in Science and Technology Librarianship)
Collaborative research is standard practice in many academic disciplines as it has been shown to increase author productivity, article quality, and publication rate. Even so, little is known about publishing patterns among academic librarians and non-library faculty who have collaborated on research. With whom are academic librarians partnering? Are there certain subjects that lend themselves to collaboration opportunities between non-library faculty and librarians? This study attempts to fill that knowledge gap by examining the nature, trends, and subject matter of peer-reviewed articles co-authored by academic librarians and non-library faculty within STEM and the health sciences. We reviewed 13 peer reviewed journals over a decade, and identified 157 co-authored articles. Within this dataset, we found that collaborations are largely affiliated with doctorate (Doctor of Philosophy and Doctor of Medicine) granting institutions where research activity is high (according to Carnegie classifications), with medical libraries and medical library journals, and in the context of collaborative instruction projects. Additionally, our data showed that ARL-affiliated librarians are more likely to publish multiple collaborative articles. Among all the collaborative articles identified, we found that the majority discussed library instruction or collaborative education projects. Other articles addressed issues related to library services and resources. Notably, we found that collaboration correlated most strongly with institution types and research areas rather than with individual institutions or individual librarians, suggesting that collaboration is a function of certain institutional characteristics and fields of study rather than individual author preferences. [ABSTRACT FROM AUTHOR]